Eryptosis and hemorheological responses to maximal exercise in athletes: Comparison between running and cycling. (14th February 2018) - Nader, E.; Guillot, N.; Lavorel, L.; Hancco, I.; Fort, R.; Stauffer, E.; Renoux, C.; Joly, P.; Germain, M.; Connes, P.
Abstract : We compared the effects of cycling and running exercise on hemorheological and hematological properties, as well as eryptosis markers. Seven endurance‐trained subjects randomly performed a progressive and maximal exercise test on a cycle ergometer and a treadmill. Blood was sampled at rest and at the end of the exercise to analyze hematological and blood rheological parameters including hematocrit (Hct), red blood cell (RBC) deformability, aggregation, and blood viscosity. Hemoglobin saturation (SpO2), blood lactate, and glucose levels were also monitored. Red blood cell oxidative stress, calcium content, and phosphatidylserine exposure were determined by flow cytometry to assess eryptosis level. Cycling exercise increased blood viscosity and RBC aggregation whereas it had no significant effect on RBC deformability. In contrast, blood viscosity remained unchanged and RBC deformability increased with running. The increase in Hct, lactate, and glucose concentrations and the loss of weight at the end of exercise were not different between running and cycling. Eryptosis markers were not affected by exercise. A significant drop in SpO2 was noted during running but not during cycling. Our study showed that a progressive and maximal exercise test conducted on a cycle ergometer increased blood viscosity while the same test conducted on a treadmill did not change this parameter because of different RBC rheological behavior between the 2 tests. We also demonstrated that a short maximal exercise does not alter RBC physiology in trained athletes. We suspect that exercise‐induced hypoxemia occurring during running could be at the origin of the RBC rheological behavior differences with cycling.